Pak Rupee As A Currency And Currency War - Hussain, Sarfraz; Rafiq, Muhammad; Quddus, Abdul; Ahmad, Nisar; Pham, Tien Phat (The journal of contemporary issues in business and government, 2021)
The purpose of this article is to discuss the daily currency wars around the world. Also, it outlines important currencies. There is a debate about the risk of currency wars and the options to handle them. The impact of the exchange rate on the Pakistani economy is also part of this debate. With less domestic savings, emerging economies such as Pakistan have to go international to get more foreign money. There are always competitors in the foreign exchange market. Fights are now commonplace. Currency wars must be recognized and dealt with properly.